Leadcare II Comparison with Graphite Furnace Atomic Absorption Spectrophotometry for Blood Lead Measurement in Peruvian Highlands - Rosales-Rimache, Jaime (2022)
“Peru is one of the countries with the highest lead contamination in the world. Biological monitoring has limitations due to the shortage of laboratories with validated methodologies for the measurement of blood lead, and it is necessary to use alternative methods for its measurement in high-altitude cities. We aimed to compare the blood lead levels (BLL) measured by the LeadCare II (LC) method and Graphite Furnace Atomic Absorption Spectrometry (GFAAS). We measured the BLL of 108 children from the city of La Oroya. The mean and median BLL for GF-AAS were 10.77 ± 4.18 and 10.44 lg/dL, respectively; for the LC method, the mean was 11.71 ± 4.28 and the median was 11.60 lg/dL. We found a positive linear correlation (Rho = 0.923) between both methods. Notwithstanding, the Wilcoxon test suggests a significant difference between both methods (q = 0.000). In addition, the Bland–Altman analysis indicates that there is a positive bias (0.94) in the LC method, and this method tends to overestimate the BLL. Likewise, we performed a generalized linear model to evaluate the influence of age and hemoglobin on BLL. We found that age and hemoglobin had a significant influence on BLL measured by the LC method. Finally, we used two nonparametric linear regression methods (Deming and PassingBablok regression) to compare the LC method with the GFAAS. We found that these methods differ by at least a constant amount, and there would be a proportional difference between both. Although in general there is a positive linear correlation, the results of both methods differ significantly. Therefore, its use in cities located at high altitudes (higher than 2440 m.a.s.l.) would not be recommended.“